HISTORY OF FORMATION AND DEVELOPMENT OF STATISTICAL SERVICE IN TURKESTAN - Beknazarov Gafur (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Statistics, Turkestan, Statistical Committee, district police officers, police officers, Zeravshan district, yearbook, reference book